Design of dual-input two phase dc/dc converter with modified pulse width modulation (mpwm) - Abu Bakar, Afarulrazi (2019)
Recently, hybrid energy source/renewable energy has attracted interest as the next-generation energy system capable of solving the problems of global warming and energy exhaustion caused by increasing energy consumption. Energy sources such as wind turbines and photovoltaic (PV) systems are intermittent, unpredictable and unregulated. For such systems, the use of multiple-input converter (MIC) has the advantage of regulating and controlling multiple-input sources. With multiple Pulsating Voltage-Source Cells (PVSC) configurations, the proposed converter can deliver power to the load individually and simultaneously. Also, it has the capability of operating either in buck, boost or buck–boost mode of operation. In addition, by proposing the enhanced Modified PWM (MPWM) switching scheme, it is able to solve the issues of the overlapping unregulated input sources. Furthermore, with the proposed multiphase configuration, the input current stresses in the switching devices are reduced and it has the benefit of a reduction in conduction losses. In addition, Zero-Voltage Switching (ZVS) technique is also employed in the proposed converter to reduce the switching loss. The proposed converter circuit is simulated by using MATLAB/Simulink and PSpice software programs. The duty cycle employed to regulate output voltage is reached from Altera DE2-70 board through dSPACE DS1103 board using by Proportional-Integral (PI) controller. The dual-input converter circuit model specification with output power at 200 W, input voltages that range from 10 to 60 V, and operating with dual switching frequencies of 50 kHz and 100 kHz is simulated to validate the designed parameters. Design guidelines, simulation and experimental results are presented. The results show that the proposed two-phase DC/DC converter with ZVS technique achieves 94% efficiency for all ranges of loads compared with the multiphase hard-switching. The total power losses across the power switches are reduced by approximately 37% in the proposed converter. Thus, the proposed converter circuit model offers advantages on input current stress and switching loss reductions. The proposed circuit configuration can be used in a standalone hybrid energy system under unregulated DC input voltages. However the major disadvantages of resonant circuit are increased peak current and voltage stress and not suitable for variable frequency operation.